Caracterización de las aguas residuales de los laboratorios de la facultad de ciencias de la salud de la universidad privada antenor orrego para un posterior tratamiento adecuado. - Vargas Rodríguez, Jorge Luis (2011)
Water is, as is widely known and recognized a basic resource for life and well-being of societies. Despite being a materially abundant substance on the surface of the Earth the differences in salinity and quality, uneven geographical distribution and a growing and composed of a variety of uses demand have made since ancient times, there is a tradition in management resource scarcity. In all countries of the world demand has increased rapidly, especially in the last 40 years. In certain cases it has exceeded the capacity for renewal of water in rivers, lakes and aquifers with negative consequences for ecosystems and humans adding to this global warming, the greenhouse effect and high pollution of waste and discharges from processes domestic, agricultural and industrial, many produce, compounds whose chemical structure differs from natural compounds, and are used as refrigerants, solvents, pesticides, plastics and detergents. The main problem with these compounds is that they are resistant to biodegradation or degrade very slowly in nature, which causes their accumulation in the environment without a safe destination or appropriate treatment.